"They Said on the Death Certificate…But Really What I Think Happened": Characterizing Cause of Death in VA Medical Centers. Issue 1 (January 2018) - Williams, Beverly Rosa; Bailey, F. Amos; Goode, Patricia S.; Burgio, Kathryn L.
Cause of death information is a vital resource for family and public health, yet significant issues persist regarding its determination, documentation and communication. In this study, we aim to characterize cause of death attribution process from the perspective of next-of-kin of Veterans who died in Veterans Affairs (VA) Medical Centers. Using a semi-structured guide, we explored next-of-kin's experiences of the Veteran's terminal hospitalization and conducted a content analysis of interview texts. In over two-third of cases next-of-kin's understanding was not consistent with their recollection of physicians' determination of cause of death. Discrepancies between official cause of death and lay understanding engendered confusion and distress. Findings have relevance for shaping the context of post-death patient/family-centered clinical practice and serve as a means for improving efficacy of cause of death communication and reducing potential for misunderstandings.